Peran Orangtua terhadap Keikutsertan Anak pada Kegiatan Keagamaan di Gampong Jeulingke, Banda Aceh - Rivaldi Zia Ulfajri; Saifullah Maysa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study aimed to determine the role of parents in children's participation in religious activities. This research is a qualitative descriptive study that describes the facts in the field, with the problem of the role of parents in children's participation in religious activities in Jeulingke Village, Banda Aceh. The data was obtained directly from parents who have children aged 6-12 years and secondary data sources, namely supporting data in this study including books, the internet, and other relevant library materials with the focus of this research. The results of the following research are: First: the role of parents in children's participation in religious activities, namely parents foster, parents train, parents make themselves role models for their children; parents give loving attention with warmth to the child; parents are responsive to children's needs; parents encourage children to be more active in participating in religious activities. Second: The role of family education (parents) is very decisive in nurturing their children.